Star Chamber Matters An Early Modern Court and Its Records - Kesselring, K. J.; Mears, Natalie (IHR Conference Series, 2021)
An extraordinary court with late medieval roots in the activities of the king's council, Star Chamber came into its own over the sixteenth and early seventeenth centuries, before being abolished in 1641 by members of parliament for what they deemed egregious abuses of royal power. Before its demise, the court heard a wide range of disputes in cases framed as fraud, libel, riot, and more. In so doing, it produced records of a sort that make its archive invaluable to many researchers today for insights into both the ordinary and extraordinary. The chapters gathered here explore what we can learn about the history of an age through both the practices of its courts and the disputes of the people who came before them. With Star Chamber, we view a court that came of age in an era of social, legal, religious, and political transformation, and one that left an exceptional wealth of documentation that will repay further study.